Export and trafficking of plasmodium proteins within the host erythrocyte (2007)
The export and trafficking of parasite proteins within the infected erythrocyte is a complex process and not well understood. Export of proteins from the parasite was previously speculated to involve a specialized compartment originally designated as the secondary endoplasmic reticulum of the Apicomplexa, or sERA. The properties of this Plasmodium export compartment are reviewed in regards to more recent observations about the trafficking of Plasmodium proteins within the host erythrocyte. In addition, a calcium ATPase unique to the Apicomplexa and with homology to the sarcoplasmic-endoplasmic reticulum calcium ATPase is discussed in the context of this unique export compartment. It is also speculated that the Plasmodium export element,PEXEL, may play a role in targeting proteins to this parasite export compartment. Exported proteins are then proposed to move into the parasit ophorous vacuoleand those destined for the host erythrocyte are transported to the erythrocytecytoplasm as soluble proteins. Chaperones probably play a role in escorting parasite proteins to their final destinations and assembly on the erythrocyte membrane.